The use of condom by the students of medical college of Barbacena a social cultural approach related to aids - Botelho, Fábio H.W.; Feres, Ângelo D.; Rezende, Dilermando F.; Câmara, Frederico G.; Pinto, Gustavo A.M.; Martins, Luciana C.F.; Costa, José O. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Background: ln recent decade, the young adults prometed a behavior sexual change, brought forward an earlier sexual activity and increased lhe number of sexual panners, causing an augmented incidcnce of lhe sexual transmiued disease (STD in lhis population. However. many researches have beco showed that usage of condom and the true levei of information about sexually transmiued disease (STD) aredcficient to gel a prcvention1u,,_ Objective: tocheck thc frequency of usage of condom among students of Medical College of Barbacena. Minas Gerais (Brazil) and to know the beliefs and students behavior conceming lhe usage of condoms. sexuality and Aids. Methods: a crosssectional study was made: a sample of 291 students nindomized from an uni verse of 427 studcnts was invcstigatcd. The students were submitted to a questionnaire, inclusive of general knowlcgdes about sexuaUy transmitlCd disease (STD)and sexuality. AII students' identities were protected. Results: ln an uni verse of29 I focussed students, 159 (55.4%) were male and 128 were female. Toe majority of panicipants were single (98.6%). About 86,3% of students havc already started thcir sexual lives. and frequently. they've been makinf usagc of condoms (75%). Conc:luslon: thc sexual profile among lhe medical students is similar, when different medical institutions are comparei'-'-'. Gencrally. men stan thcir sexual activity carlier lhan womcn, and make sex with a higher number of sexual panners. Again, the usage of condom is much more frequent in lhe malc population.